Asālīb Bināi Manhaj At-Ta‘allum Al-Madji ‘Alā Asās Al-Madkhal Al-Itisālī Li Tanmiyati Mahārāt Al-Lugah Al-‘Arabiyyah Li Nātiqīna Bi Gairihā - Mohammad Ismail (University of Darussalam Gontor, 2019)
Asālīb Bināi Manhaj At-Ta‘allum Al-Madji ‘Alā Asās Al-Madkhal Al-Itisālī Li Tanmiyati Mahārāt Al-Lugah Al-‘Arabiyyah Li Nātiqīna Bi GairihāMoh. IsmailUniversity of Darussalam Gontorismail@unida.gontor.ac.idAbstractArabic language teaching for non-Arabs requires seriousness in four skills that are listening, speaking, reading, and writing. Arabic teachers are expected to give more attention to using modern technology when teaching those skills. Because technology is a good media of communication between teachers and students. Technology has a major role in improving Arabic proficiency for non-Arabs. Technology can make the learning process easier than traditional leaning methods. There are many types of learning Arabic using technology, and one of that is